Evaluation of Classrooms in terms of Objective Parameters of Sound: KTÜ Case - Kavraz, Mustafa; Kabil, Öznur (Fırat University, 2020)
In the ergonomic design of places, physical indicators such as heat, temperature, humidity, light and sound should be provided in optimum conditions. Sound, which has an important place among the physical indicators, should not be perceived as noise but should be perceived in auditory boundaries depending on the function in places. The determination of this situation can be realized by acoustic control for the places. In this study, acoustical conditions in Classroom 270 in Civil Engineering and D-3 Classroom in Forest Engineering in KTU were evaluated according to the objective parameters of sound. Odeon Version 10 Software program were used for evaluations. In the studyi the objective parameters of sound which are reverberation time (RT), early fall time (EDT), clarity (D50) and the intelligibility index (STI) were investigated. Firstly, the objective parameter values of the sound were obtained for the current spaces and material changes were made on the surfaces of the spaces in order to obtain at the optimum limits to the parameters at outside the optimum range. After the material changes, the optimum conditions were obtained in terms of acoustic.

Mekânların ergonomik tasarımlarında sıcaklık, nem, ışık, ses gibi fiziksel göstergelerin optimum koşullarda sağlanması gerekmektedir. Fiziksel göstergeler arasında önemli bir yere sahip olan sesin, gürültü olarak algılanmamasının yanı sıra mekânlarda fonksiyona da bağlı olarak işitsel sınırlar içinde algılanması gerekmektedir. Bu durumun belirlenebilmesi ise mekânlar için yapılacak akustik denetim ile gerçekleştirilebilmektedir. Bu çalışma kapsamında KTÜ İnşaat Mühendisliği 270 No’lu ve Orman Mühendisliği D-3 No’lu Dersliklerdeki akustik koşullar sesin nesnel parametrelerine göre değerlendirilmiştir. Değerlendirmeler için Odeon Version 10 Software programı kullanılmış olup çalışmada; reverberasyon süresi (RT), erken düşme süresi (EDT), belirginlik (D50), sesin anlaşılabilirlik indeksi (STI) nesnel parametreleri incelenmiştir. Öncelikle mevcut mekânlara ait nesnel parametre değerleri elde edilmiş olup optimum aralık dışında kalan parametrelerin optimum sınırlarda elde edilebilmesi için mekânların yüzeylerinde malzeme değişiklikleri yapılmıştır. Malzeme değişiklikleri sonrasında akustik açıdan optimum koşullar elde edilmiştir.
Dersliklerin Sesin Nesnel Parametreleri Açısından Değerlendirilmesi: KTÜ Örneği
Keywords: Engineering; Mühendislik